The Pathogenesis of HCC Driven by NASH and the Preventive and Therapeutic Effects of Natural Products - Shao, Gaoxuan; Liu, Ying; Lu, Lu; Zhang, Guangtao; Zhou, Wenjun; Wu, Tao; Wang, Lei; Xu, Hanchen; Ji, Guang (Frontiers in Pharmacology, 2022)
Nonalcoholic steatohepatitis (NASH) is a clinical syndrome with pathological changes that are similar to those of alcoholic hepatitis without a history of excessive alcohol consumption. It is a specific form of nonalcoholic fatty liver disease (NAFLD) that is characterized by hepatocyte inflammation based on hepatocellular steatosis. Further exacerbation of NASH can lead to cirrhosis, which may then progress to hepatocellular carcinoma (HCC). There is a lack of specific and effective treatments for NASH and NASH-driven HCC, and the mechanisms of the progression of NASH to HCC are unclear. Therefore, there is a need to understand the pathogenesis and progression of these diseases to identify new therapeutic approaches. Currently, an increasing number of studies are focusing on the utility of natural products in NASH, which is likely to be a promising prospect for NASH. This paper reviews the possible mechanisms of the pathogenesis and progression of NASH and NASH-derived HCC, as well as the potential therapeutic role of natural products in NASH and NASH-derived HCC.